Hematological Indices as Surrogate Markers in Hypertension: an Observational Clinical Study - Al-Nimer, Marwan; Hussein, Ismail (Jordan Medical Journal, 2016)
Hematological indices are used as markers for diagnostic and prognostic purposes in medicine. Aims: This study aimed to assess the levels of hematological indices in hypertensive patients taking in consideration the status of the blood pressure control and the metabolic derangements. Materials and Methods: A total number of 82 hypertensive patients were enrolled in this study. They were grouped into Group I (controlled hypertension, n=14)) and Group II (Uncontrolled hypertension, n=68). Anthropometric measurements, fasting serum lipid profile, and hematological indices were determined. Results: Significant high serum levels of triglyceride were observed among Group II. There is insignificant difference between Group I and II in the hematological indices. Group II patients showed a significant correlation of plateletcrit (PCT) with mean arterial pressure, and platelet distribution width (PDW) with triglycerides. In Group I, a significant positive correlation between PCT with body mass index, and mean platelet volume (MPV) with cholesterol and apolipoprotein B100 were observed. Conclusion: We conclude that the MPV values tended to be lower while the PCT is higher than the normal values in hypertension whether controlled or uncontrolled. The red blood cell width (RDW) values do not discriminate between controlled and uncontrolled hypertension.